Gut microbiota-derived metabolites in inflammatory diseases based on targeted metabolomics - Xu, Hui; Pan, Li-Bin; Yu, Hang; Han, Pei; Fu, Jie; Zhang, Zheng-Wei; Hu, Jia-Chun; Yang, Xin-Yu; Keranmu, Adili; Zhang, Hao-Jian; Bu, Meng-Meng; Jiang, Jian-Dong; et al. (Frontiers in Pharmacology, 2022)
The gut microbiota plays an important role in inflammatory diseases. Metabolites in the three metabolic pathways of tryptophan (Trp), histidine (His) and phenylalanine (Phe) can affect various inflammatory conditions, such as obesity, diabetes, arthritis, colitis, atherosclerosis, and neuroinflammation. We established an LC–MS/MS method to measure 17 inflammatory biomarkers, including tryptophan (Trp), 3-indole-acetic acid (Iaa), 3-indole-lactate (Ila), 3-indole-propionic acid (Ipa), 3-indole formaldehyde (Iald), kynurenine (Kn), kynurenic acid (Kyna), 3-hydroxybenzoic acid (3-Haa), histidine (His), 3-methylhistidine (3-Mhis), histamine (Hist), imidazole propionic acid (Imp), 4-imidazoacetic acid (Imaa), urocanic acid (Ua), phenylalanine (Phe), phenylethylamine (Pea), and hippuric acid (Ha), in the three metabolic pathways. The method exhibited high sensitivity and good selectivity, linearity, accuracy, precision, stability and recovery rate, all meeting the requirements of biological sample analysis. By establishing a rheumatoid arthritis (RA) model and performing 16S rRNA sequencing on the feces, it was found that there was dysbiosis. The contents of the microbiota metabolites Iaa and Ipa in the model group were significantly decreased, and those of Iald, Kn, Kyna, Ha and Imp were significantly increased. The common therapeutic drugs Tripterygium glycosides, total glucosides of peony and their main active ingredients were screened by incubation outside the bacterial population, and it was found that Tripterygium glycosides and their active ingredients have regulatory effects on the tryptophan and phenylalanine pathways. Total glucosides and active components of peony can regulate the phenylalanine pathway of the gut microbiota.